42 Practicalities of delivering in situ simulation in a tertiary centre. (17th November 2016) - Farooq, O; Purva, M; Purva, M
Abstract : There is emerging evidence that in situ simulation (simulation in workplace) helps in reduction of morbidity and mortality. We delivered a multi professional, multi disciplinary in situ simulation (ISS) across various acute specialties in tertiary hospital. We would like to share our experience in setting up and effective running of this programme. Methods: As part of study project, we completed integrated research application (IRAS) form. Approval from clinical directors through emails and telephonic communication was sorted. It took around 2 months for approval process to complete. Emergency scenarios across 5 specialties namely anaesthetics, obstetrics, gynaecology, A&E and acute medicine, were delivered. 15 minutes of scenario followed by 30 minutes of video assisted debriefing were conducted. Immediate reporting of latent errors (hidden errors in the system) were fed back to the parent department and necessary changes were introduced in the system. Results: Initial approval took longer than expected. Educational needs analysis with parent team was pivotal in delivering of effective programme but required plenty of rescheduling to gather all stakeholders. Few sessions got cancelled due to patients' need. Some managers did not buy in the idea of simulation and provided relentless resistance that led us to cancel ISS and provide basic drills training. Educational enthusiasts would go to great lengths to promote learning and provide assistance. With technical team support, video assisted feedback helped us highlight good practice points. Conclusion: Conducting ISS across various specialties was very rewarding. We received very positive feedback. Due limited guidance on setting up ISS, we developed ISS toolkit and video, to highlight important components.Most of the participants once involved appreciated the importance of ISS and were keen to have regular training sessions.More work is required to deliver ISS in non acute services as this would help in better training opportunities across board.